2015
DOI: 10.1200/jco.2014.60.6327
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Intergroup Trial of Alisertib in Relapsed and Refractory Peripheral T-Cell Lymphoma and Transformed Mycosis Fungoides: SWOG 1108

Abstract: Purpose Aurora A kinase (AAK) is upregulated in highly proliferative lymphomas, suggesting its potential as a therapeutic target. Alisertib is a novel oral AAK inhibitor without adverse safety signals in early-phase studies that demonstrated preliminary activity in T-cell lymphoma. This phase II study was conducted to further investigate the efficacy of alisertib in relapsed or refractory peripheral T-cell non-Hodgkin lymphoma (PTCL). Patients and Methods Eligible patients with histologically confirmed relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 25 publications
2
72
0
1
Order By: Relevance
“…50%) 241 and in combination with bortezomib (a proteasome inhibitor) in multiple myeloma (response rate 27%) 242 . Moreover, two clinical phase II studies reported promising anti-tumour activity in relapsed/refractory B-cell and T-cell non-Hodgkin lymphoma (response rate 27%) 243 and in relapsed/refractory peripheral T-cell lymphoma (response rate 30%) 244 . The potential clinical benefit for patients with peripheral T-cell lymphoma is currently being investigated in a phase III trial (see Supplementary Information S1 (table)).…”
Section: Targeting Of Other Cell Cycle Proteinsmentioning
confidence: 99%
“…50%) 241 and in combination with bortezomib (a proteasome inhibitor) in multiple myeloma (response rate 27%) 242 . Moreover, two clinical phase II studies reported promising anti-tumour activity in relapsed/refractory B-cell and T-cell non-Hodgkin lymphoma (response rate 27%) 243 and in relapsed/refractory peripheral T-cell lymphoma (response rate 30%) 244 . The potential clinical benefit for patients with peripheral T-cell lymphoma is currently being investigated in a phase III trial (see Supplementary Information S1 (table)).…”
Section: Targeting Of Other Cell Cycle Proteinsmentioning
confidence: 99%
“…Responses were seen in patients who failed prior pralatrexate or HDAC-inhibitor treatment and in nearly half of those who showed disease refractoriness. 73 On the basis of these results, phase 3 randomized trials comparing alisertib with the investigator's choice (gemcitabine, pralatrexate, romidepsin) in relapsed or refractory PTCL patients is ongoing (#NCT01482962); according to preliminary results, however, no significant efficacy benefit of alisertib vs comparators has been documented. 74 …”
Section: Org Frommentioning
confidence: 99%
“…Despite these disappointing data, other studies in breast cancer, small cell lung cancer, and peripheral T-cell lymphoma have reported promising activity with the use of alisertib. 28,31 These findings provide initial validation of the aurora A kinase as a potentially important drug target in certain cancer types.…”
Section: Discussionmentioning
confidence: 82%